2021
DOI: 10.2478/hukin-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Activation with Variable Intra-Repetition Resistance on Throwing Velocity in Female Handball Players: A Methodological Proposal

Abstract: The purpose of this study was to investigate the acute effect of pre-activation with Variable Intra-Repetition Resistance and isometry on the overhead throwing velocity in handball players. Fourteen female handball players took part in the study (age: 21.2 ± 2.7 years, experience: 10.9 ± 3.5 years). For Post-Activation Potentiation, two pre-activation methods were used: (I) Variable Intra-Repetition Resistance: 1 x 5 maximum repetitions at an initial velocity of 0.6 m·s-1 and a final velocity of 0.9 m·s-1; (II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…In contrast, an ~ 2.8%; ES = 0.14 improvement in power output in the BBT was found following 1 repetition of isometric bench press of a 7-s duration [ 35 ]. A standing isometric chest press variation did not elicit PAPE in experienced handball players [ 46 ], observed as no improvements in overhead handball throwing velocity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an ~ 2.8%; ES = 0.14 improvement in power output in the BBT was found following 1 repetition of isometric bench press of a 7-s duration [ 35 ]. A standing isometric chest press variation did not elicit PAPE in experienced handball players [ 46 ], observed as no improvements in overhead handball throwing velocity.…”
Section: Resultsmentioning
confidence: 99%
“…It could, therefore, also be plausible that the single measurement at 4 min [ 55 ] may not have been sufficient recovery to reduce fatigue from the multiple repetitions of 90%1RM bench press. The same limitations applied to a study by Martinez-Garcia et al [ 46 ], who found no significant improvements in overhead handball throwing velocity following a standing chest press with variable resistance, with even shorter initial recovery durations. Markovic et al [ 33 ] also found bench press produced non-significant differences in throwing performance 3 min following the conditioning activity, where the medicine ball load (0.55-kg) was similar to that of a handball.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the softball players and other overhead athletes are using advanced training methods like post-activation performance enhancement (PAPE) in long-term training programs. PAPE is an efficient method for an acute increase in explosive strength [ 2 6 ], which requires a precise selection of conditioning activity (CA) [ 7 , 8 ]. Although PAPE is based on post-activation potential which increases the sensitivity of actomyosin filaments to Ca 2+ , enhances recruitment of higher-order motor units, and changes in pennation angle [ 9 , 10 ], the exercise selection is one of the key factors to modulate the magnitude of PAPE [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Female athletes exhibit different muscle activity during bench press exercises than men [ 29 ], and therefore same conditioning might bring different results. It has been shown that 86% of women handball players are PAPE responders in throwing velocity to variable resistance intra-repetition method, and 93% of them positively respond to isometric CA [ 6 ]. In the exercise selection studies, the bench press (BP) CA increased throw distance in women's shot put [ 26 ], and maximal rowing exercise increased rowing speed [ 30 ] with the same PAPE effect for males and females rowers.…”
Section: Introductionmentioning
confidence: 99%
“…A number of potential mechanisms included, but is not limited to, increased phosphorylation of the myosin light chain, increases in muscle temperature, increases in muscle blood flow/water content and increased muscle activation ( Blazevich and Babault, 2019 ). In practical settings, strength and conditioning practitioners commonly prescribe complex training by manipulating PAPE mechanisms to further improve power performance (e.g., a set of back squats followed by a set of plyometrics) ( Cormier et al, 2020 ; Martínez-García et al, 2021 ; Pagaduan and Pojskic, 2020 ). Therefore, it is conceivable that utilizing VRT within a complex training program might be more effective in enhancing power adaptation.…”
Section: Introductionmentioning
confidence: 99%